Tribological and morphological properties of bentonite nano-clay/CaCO3 reinforced high-density polyethylene nanocomposites - Salit @ Sinon, Mohd Sapuan; Ahmad, Tauseef; Alam, Mohammad Azad; Ya, Hamdan; Mohammad Azeem, .; M. Rehan Khan, .; Mohammad Yusuf, .; Afridi, Junaid (John Wiley & Sons, 2024)
Elastomeric polymers such as high-density polyethylene, have a variety of desirable features, that have supplanted traditional materials. However, high-density polyethylene (HDPE) shows inadequate wear resistance, which limits its use for industrial applications, particularly in low-load-bearing applications such as flexible energy harvesting devices and sensors. The current work is engrossed in investigating the influence of hybrid reinforcements CaCO3 particles and bentonite nano clay as secondary reinforcements in high-density polyethylene (HDPE)-based composites on the wear and friction properties. The reinforcements were melt compounded with HDPE using a Brabender mixer and sampled using an injection molding machine. The wear test (ASTM G-99-04) was performed by a pin-on-disk tribo-tester. In comparison to a base matrix, the synthesized hybrid composite achieved the maximum improvement in wear rate of 93%. The results revealed that there is a significant improvement in wear resistance. Morphological analysis revealed that due to the encapsulation and compatibilization effect of bentonite nano clay the hybrid composite exhibited improved wear performance. The results signify the synergistic effect of filler particles resulted in sufficient bonding for stress transfer due to the encapsulation of CaCO3 by nano clay. The wear mechanism observed optically was abrasion, fatigue, and adhesion wear that changed with the change in the weight percent of nanoparticles. Finally, the prepared composite with enhanced tribological properties such as low wear rate, low friction coefficient, and enhanced morphology can be used in low load-bearing wear applications such as turbo nanogenerators and piezo nanogenerators.